Breaking dormancy in Cycas revoluta: A study of seed morphological characterization and dormancy mechanisms - Juliana Maria Espíndola Lima; João Almir Oliveira (Journal of Seed Science)
ABSTRACT: Cycas revoluta seeds exhibit both physical and morphological dormancy, posing significant challenges to their germination. This study investigated the morphological characteristics and dormancy mechanisms of C. revoluta seeds and evaluated methods to overcome these dormancies. Seeds were harvested over two consecutive years and subjected to different treatments. A morphological analysis of seed structure was conducted, along with assessments of physical (seed size, weight, and moisture content) and physiological tests (germination rate, germination speed, and mean time of germination).Morphological characterization revealed that the thick, woody sclerotesta forms an impermeable barrier, while the embryos within are often underdeveloped at the time of seed maturity. Germination of the first year demonstrated that removing the sclerotesta significantly enhances germination rates, with naked seeds achieving a 70% germination rate at 30 °C. In the second year, soaking naked seeds in gibberellic acid at 200 ppm for 24 hours further promoted germination, though its effect was modest compared to sclerotesta removal (naked seed). This study also demonstrated that storing seeds for a year allowed embryos to complete their development, further improving germination outcomes. These findings suggested that mechanical removal of the sclerotesta, combined with optimal storage conditions, is an effective strategy for overcoming dormancy in C. revoluta seeds and soak time in gibberellic acid (200 ppm) or water for 24 hours could enhance germination as well.